2010
DOI: 10.1016/j.neuroscience.2010.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Sulforhodamine 101 induces long-term potentiation of intrinsic excitability and synaptic efficacy in hippocampal CA1 pyramidal neurons

Abstract: Sulforhodamine 101 (SR101) has been extensively used for investigation as a specific marker for astroglia in vivo and activity-dependent dye for monitoring regulated exocytosis. Here, we report that SR101 has bioactive effects on neuronal activity. Perfusion of slices with SR101 (1 μM) for 10 min induced long-term potentiation of intrinsic neuronal excitability (LTP-IE) and a long-lasting increase in evoked EPSCs (eEPSCs) in CA1 pyramidal neurons in hippocampal slices. The increase in intrinsic neuronal excita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…1C). Astrocytes were readily detected by two-photon imaging after the slice had been incubated with the fluorescent dye Texas red hydrazide, an approach similar to that described for sulphorhodamine 101 (11,12). Dye loading of slices obtained from transgenic mice that express EGFP under control of the Glt-1 promoter (Glt-1-EGFP BAC transgenic mice) (13) confirmed that Texas red hydrazide was selectively taken up by GFP-expressing astrocytes (Fig.…”
Section: Aqp4 Deletion Reduces Swelling Of Cortical Astrocytes Exposementioning
confidence: 81%
“…1C). Astrocytes were readily detected by two-photon imaging after the slice had been incubated with the fluorescent dye Texas red hydrazide, an approach similar to that described for sulphorhodamine 101 (11,12). Dye loading of slices obtained from transgenic mice that express EGFP under control of the Glt-1 promoter (Glt-1-EGFP BAC transgenic mice) (13) confirmed that Texas red hydrazide was selectively taken up by GFP-expressing astrocytes (Fig.…”
Section: Aqp4 Deletion Reduces Swelling Of Cortical Astrocytes Exposementioning
confidence: 81%
“…1A) (11,17). Astrocytes were identified by enhanced green fluorescent protein (eGFP) expressed under the Glt1 promoter, which helped us avoid the use of the epileptogenic dye sulforhodamine (SR)101 (18,19). This labeling also Author contributions: A.S.T., V.R.T., E.A.N., and M.N.…”
Section: General Anesthetics Suppress Calcium Transients In Neocorticalmentioning
confidence: 99%
“…While it has been known for many years that astrocytes preferentially take up AM ester Ca 2+ indicators, the secondary marker SR-101 is often used to verify the loaded cells as astrocytes. SR-101 may in itself alter the intrinsic excitability of neurons 29 . Use of SR-101 corroborates the need to perform all astrocyte Ca 2+ measurements in TTX to limit possible SR-101 effects on neuronal excitability.…”
Section: Discussionmentioning
confidence: 99%